Reproductive biology of Phragmipedium longifolium and floral anatomy associated with pollinator attraction in the genus - Díaz Morales, Melissa (2019)
Phragmipedium is a genus with 21 species restricted to the tropics and subtropics from Central and South America. As it is a genus capable of producing seeds from both self- and cross-pollinated flowers, it is an ideal group to investigate the components of its reproductive success. In this research some of those components are described in P. longifolium as well as anatomical floral structures possibly related to the attraction of pollinators. To study the reproductive system in P. longifolium, manual self- and cross-pollinations were carried out, and seed viability was measured by tetrazolium staining. No significant differences in fruit production between self- and cross-pollinated flowers were found. Higher seed viability was found in the self-pollinated flowers, which indicates that this species is frequently self-pollinated. Sections of the petals of P. humboldtii, P. longifolium, and P. warzewiczianum were stained with toluidine blue in order to identify and characterize anatomical structures possibly involved in the attraction of pollinators. Three kinds of glandular trichomes were observed on the petals of all three species, which are possibly involved in the secretion of fragrances to attract pollinators.